Analisis Penyelesaian Pembiayaan Kredit Pemilikan Rumah (KPR) Bermasalah (Studi Pada Bank BTN Kantor Cabang Syariah Medan) - Ruhiya Azarita Br Ginting; Muhammad Amri Nasution; Al Firah (Universitas Dharmawangsa, 2026)
This research aims to analyze the causes of problematic Home Ownership Credit (KPR) financing and find out the resolution strategies used by Bank BTN Syariah Medan Branch Office in handling this financing. The application of Home Ownership Credit (KPR) financing is popular with many people to own a house with the risk of financing problems which can affect the performance and stability of the bank. This research uses research methods with a qualitative approach, with data collection techniques including observation, interviews and documentation. Research informants include internal bank personnel who handle financing and customers who experience problematic Home Ownership Loan financing. The research results show that the causes of problematic Home Ownership Loan financing are influenced by two factors, namely internal factors related to the customer's personal circumstances such as decreasing income, lack of financial management skills, and indiscipline in making installment payments and external factors including economic conditions, increasing living costs, and unexpected expenses which affect the customer's ability to fulfill their obligations. In resolving problematic Home Ownership Loan financing, Bank BTN Syariah Medan Branch Office applies several resolution strategies, such as a persuasive approach to customers, restructuring financing through rescheduling, reconditioning and restructuring, as well as settlement through collateral auctions as a last resort if customers are unable to fulfill their obligations.